688 Cancellation Rate of Prostate Template Biopsy: Are There Any Merits to Implementing Pre-Operative Bowel Preparations?. (12th October 2021) - Lim, P; Damola, A; Apakama, I
Abstract: Introduction: The aim of this quality improvement project was to analyse the cancellation rates of the template biopsy done at the George Eliot Hospital. The focus was mainly on those due to poor bowel prep whereby manual evacuations have failed. Locally we have sometimes noted the failure rate of transperineal prostate biopsy as a result of the poor quality of the ultrasound due to inadequately evacuated rectum. Unfortunately, there are very limited studies which have looked into this issue hence the significance of this problem is not universally acknowledged. Method: Retrospective review of all the template biopsies that were planned from April 2019 to April 2020 using the operation notes and local theatre management software. Results: There was a total of 105 planned template biopsies from April 2019 to April 2020. 72 cases were attempted and within this, 7 of these cases required manual evacuations in which 3 resulted in abandonment of procedure. There were 33 cases which were cancelled due various other reasons. Conclusions: The results showed that the failure rates due to poor bowel prep were not significant (4%). Based on these findings we have decided not to proceed with the implementation of pre-operative bowel prep with phosphate enema as we felt that the potential benefits were not enough for it be initiated as a routine practice. We aim to address the other reasons identified for cancellations.